2007
DOI: 10.1103/physrevlett.98.158702
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Non-Poissonian Activity Patterns on Spreading Processes

Abstract: Halting a computer or biological virus outbreak requires a detailed understanding of the timing of the interactions between susceptible and infected individuals. While current spreading models assume that users interact uniformly in time, following a Poisson process, a series of recent measurements indicates that the intercontact time distribution is heavy tailed, corresponding to a temporally inhomogeneous bursty contact process. Here we show that the non-Poisson nature of the contact dynamics results in prev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

18
350
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 322 publications
(368 citation statements)
references
References 26 publications
18
350
0
Order By: Relevance
“…Thus, the slowing-down effect can be explained by characterizing the timings of the call sequences of links. For this, we have used the concept of relay times [4,6], and showed how the burstiness and the slow spreading speed compared to the Poisson process are equivalent concepts: the slowing down is due to the bursty nature of the event sequences. We also found that there is a lot of heterogeneity in the relay times of links even when normalizing by weight; thus not only the broad distribution of link weights but also the distribution of relay times affects the speed of spreading.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, the slowing-down effect can be explained by characterizing the timings of the call sequences of links. For this, we have used the concept of relay times [4,6], and showed how the burstiness and the slow spreading speed compared to the Poisson process are equivalent concepts: the slowing down is due to the bursty nature of the event sequences. We also found that there is a lot of heterogeneity in the relay times of links even when normalizing by weight; thus not only the broad distribution of link weights but also the distribution of relay times affects the speed of spreading.…”
Section: Discussionmentioning
confidence: 99%
“…In this approximation, the relay times τ R of a link are determined purely by the inter-event time distribution of events on that link, P (τ ), where the inter-event time τ is defined as the time difference between two consecutive events. On the basis of the inter-event time distribution, the probability distribution of the relay times can be written as [4]. Further, assuming that the tail of the distribution is not too broad (lim x→∞ x 2 P (τ > x) = 0), the average relay time τ R can be calculated analytically for any inter-event time distribution:…”
Section: Spreading Speed On Single Linksmentioning
confidence: 99%
See 3 more Smart Citations